HWL‐088, a new potent free fatty acid receptor 1 (FFAR1) agonist, improves glucolipid metabolism and acts additively with metformin in ob/ob diabetic mice. (8th February 2020) - Chen, Yueming; Ren, Qiang; Zhou, Zongtao; Deng, Liming; Hu, Lijun; Zhang, Luyong; Li, Zheng
Abstract : Background and Purpose: The free fatty acid receptor 1 (FFAR1) plays an important role in glucose‐stimulated insulin secretion making it an attractive anti‐diabetic target. This study characterizes the pharmacological profile of HWL‐088 (2‐(2‐fluoro‐4‐((2′‐methyl‐[1, 1′‐ biphenyl]‐3‐yl)methoxy)phenoxy)acetic acid), a novel highly potent FFAR1 agonist in vitro and in vivo. Moreover, we investigated the long‐term effects of HWL‐088 alone and in combination with metformin in diabetic mice. Experimental Approach: In vitro effects of HWL‐088 on FFAR1 and PPARα/γ/δ were studied in cell‐based assays. Glucose‐dependent insulinotropic effects were evaluated in MIN6 cell line and in rats. Long‐term effects on glucose and lipid metabolism were investigated in ob/ob mice. Key Results: HWL‐088 is a highly potent FFAR1 agonist (EC50 = 18.9 nM) with moderate PPARδ activity (EC50 = 570.9 nM) and promotes glucose‐dependent insulin secretion in vitro and in vivo. Long‐term administration of HWL‐088 exhibited better glucose control and plasma lipid profiles than those of another FFAR1 agonist, TAK‐875, and synergistic improvements were observed when combined with metformin. Moreover, HWL‐088 and combination therapy improved β‐cell function by up‐regulation of pancreas duodenum homeobox‐1, reduced fat accumulation in adipose tissue and alleviated fatty liver in ob/ob mice. The effect of HWL‐088 involves a reduction in hepatic lipogenesis and oxidative stress, increased lipoprotein lipolysis, glucose uptake, mitochondrial function and fatty acid β‐oxidation. Conclusion and Implications: These data indicate that long‐term treatment with HWL‐088, a highly potent FFAR1 agonist, improves glucose and lipid metabolism and may be useful for the treatment of diabetes mellitus by mono‐therapy or combination with metformin.